The Effectiveness of Effleurage Back Massage Therapy on Pain, Pulse, Systolic Blood Pressure, Diastolic Blood Pressure, and Respiration among Post-Operative Clients in Selected Hospitals, Andhra Pradesh - Kanakalakshmi, S. (Indian Journal of Nursing Sciences, 2024)
Background of the Study: The pain alters the quality of life and pain management can lead to many consequences affecting the client. Effleurage back massage can have mechanical, neurological, psychological, and reflexive effects. Aim: The aim of the study was to assess the effectiveness of effleurage back massage on pain and physiological parameters among post-operative clients. Method: The study was quantitative evaluative approach with quasi-experimental time series design. Purposive sampling technique was used to select 200 post-operative clients. Experimental group and control group consisted of 100 samples each. Reliability of the tool was elicited using inter-rater method and it was found to be reliable, r = 1. The data were collected by interview schedule and measurement 1st–5th postoperative day twice in a day. An intervention of effleurage back massage with talcum powder was given morning and evening for 10–15 min to the experimental group over a period of 5 days from 1 to 5 post-operative day. Results: The results in the experimental group showed that the 1st day pulse pre–test mean score was 113.04 which was reduced to 108.86 by 5-day post-test score, systolic blood pressure (BP) mean score was 136.54 which was reduced to 112.06, diastolic BP mean score was 76.92 which was reduced to 72.82, and respiratory rate mean score was 31.52 which was reduced to 26.269 by the 5th day post-test scores and was found to be a non–significant showing not much effect on physiological parameters. Conclusion: The experimental group sample received effleurage back massage twice in a dayfrom 1stpost -operative day to 5thpost - operative day, levels were analyzed, in the controlgroup sample not given effleurage back massage, levels were analyzed. Control groupvalues did not show an significant difference between pre-test and post-test.Experimental group values pain was significant difference between pre-test and posttest